IDENTIFIKASI TENTANG PENGGUNAAN BAHAN AJAR PADA MATA PELAJARAN PRODUKTIF AKUNTANSI DI KELAS X AKUNTANSI SMK NEGERI 4 SURABAYA - ELLA AQUIN DARMA M Y (Jurnal Pendidikan Akuntansi (JPAK), 2013)
This research has purpose to find out the teaching material that is used by teacher of Accounting Tenth Class in Surabaya State Vocational High School 4, the teacher reason in using that teaching material and find out the teaching material feasibilty that is used. This research kind is descriptive research with quantitative approach. This research result shows that teaching material that is used by teacher is An Accounting Lesson Book for SMK Tenth Class KTSP Edition, written by Toto Sucipto, dkk. Teacher uses that book because the content is systematic, easy to understand, suitable with the school curriculum and syllabus, and also the book price is achievable. Based on the analysis of teaching material feasibilty gotten result that the teaching material that used by teacher on productive accounting lesson in first accounting tenth class Surabaya State Vocational High School 4 is very feasible if used as teaching material in learning process. Keywords: Feasibility, Teaching Material.